Ambidexterity and human resource management: a paradigmatic and methodological review. (22nd June 2022) - Akbar, Hinadi; Khan, Ahmad Faraz; Talib, Parvaiz
This paper reviews the research work carried out in the field of ambidexterity and human resource management during the decade (2008-2018). This paper reviews research work from a paradigmatic and methodological approach. The study analyses the selected contributions from the perspective of operations research paradigm framework (Meredith et al., 1989). It further compares and contrasts various research articles, methodologies, and research designs used in various studies. Using relational analysis approach recurrent themes are identified and research clusters are formed. The analysis leads to identification of five major research clusters namely, definitions and models of ambidexterity, approaches to ambidexterity, ambidexterity and related constructs, ambidexterity and HRM and impact of ambidexterity on performance. This study is a maiden attempt to provide a comprehensive picture of the extant literature focusing on human resource dimensions in ambidexterity research. This study provides greater insights by using a research paradigm framework to summarise the literature.